Sistem Informasi Perpustakaan Menggunakan Barcode Berbasis Web - yati nurhayati (NUANSA INFORMATIKA, 2019)
The library as one of the media that provides a variety of reliable sources of knowledge in the form of books, journals and other scientific research. To increase interest in reading, especially in students and lecturers, the library needs to be supported by a system that can manage library data quickly and accurately. At this time, especially in the University of Kuningan Faculty of Computer Science Library the existing library application still has several obstacles, namely the system cannot display the existing book stock and the number of books borrowed making it difficult for librarians and students to check stock, for input and search books are still input by typing it so that it is inefficient, to search for books in other faculties' libraries, they must choose the first keywords that are searched so that they must check one by one in various faculties, there is no division of categories between books, journals or theses and the resulting reports are not optimal . The results of this study are in the form of an information system in which librarians can manage collection data in the form of books, journals, student / lecturer research results (practical work reports / thesis proposals / final assignments / theses / dissertations), other collections (such as magazines , newspapers, etc.), management of borrowing and returning books, management of library members, guest books and reports (available books, borrowed, etc.). The system developed can read book codes and member codes in the form of barcodes to facilitate data search when borrowing / returning transactions occur. Each book has one barcode, where the same title (including the author, publisher and published year) has the same code, the code is only the back for each book, so that the book can be borrowed / available / lost. even though the title is the same. This system is designed using DFD and developed using the RAD method. The design results are applied to the PHP and MySQL programming languages. This information system can be used by all librarians in all faculties in Kuningan University and Kuningan University librarians, where each admin / user can only manage data in each work unit.. Keywords— Library, DFD, Barcode, MySQL, Information System